2022
DOI: 10.1101/2022.07.28.499225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impairments in the mechanical effectiveness of reactive balance control strategies during walking in people post-stroke

Abstract: People post-stroke have an increased risk of falls compared to neurotypical individuals, partly resulting from an inability to generate appropriate reactions to restore balance. However, few studies investigated the effect of paretic deficits on the mechanics of reactive control strategies following forward losses of balance during walking. Here, we characterized the biomechanical consequences of reactive control strategies following perturbations induced by the treadmill belt accelerations. Thirty-eight post-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Wang & Srinivasan, (2014) showed that CoM states at mid-stance and heel strike predict about 33% of the variance in AP foot placement. Recently, Liu, (2021) replicated this finding in steady-state walking and additionally in perturbed walking. This study by Liu revealed that a different foot placement model is needed to describe responses to slip-like and trip-like treadmill perturbations, suggesting that the control of foot placement may be different between steady-state and perturbed walking.…”
Section: Introductionmentioning
confidence: 68%
“…Wang & Srinivasan, (2014) showed that CoM states at mid-stance and heel strike predict about 33% of the variance in AP foot placement. Recently, Liu, (2021) replicated this finding in steady-state walking and additionally in perturbed walking. This study by Liu revealed that a different foot placement model is needed to describe responses to slip-like and trip-like treadmill perturbations, suggesting that the control of foot placement may be different between steady-state and perturbed walking.…”
Section: Introductionmentioning
confidence: 68%
“…The independent dataset used to validate the final models consisted of 23 neurotypical adults (age: 61 ± 15 years (24-77 years); leg length: 0.78 ± 0.06 meters (0.67-0.88 meters); mass: 72 ± 18 kg (37-103 kg)) walking at their self-selected speed (0.48 to 1.29 m/s) for 2-5 minutes. These data were collected as part of another study, and the kinetic and kinematic data collection procedures have been previously reported [31]. Kinematic data were recorded at 100 Hz and kinetic at 1000 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…We defined leg length as the vertical distance from the greater trochanter marker to the lateral malleolus marker while the participant stood upright. Please see the previous publications [30,31] for additional information about the data collection procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The independent dataset used to validate the final models consisted of 22 neurotypical adults (age: 61 ± 15 years (24-77 years); leg length: 0.78 ± 0.06 m (0.67-0.88 m); mass: 73 ± 18 kg (37-103 kg)) walking at their self-selected speed (0.48 to 1.29 m/s) for 2-5 min. These data were collected as part of another study, and the kinetic and kinematic data collection procedures have been previously reported 47 . Kinematic data were recorded at 100 Hz and kinetic at 1000 Hz.…”
Section: Independent Validation Datasetmentioning
confidence: 99%